The Evaluatıon Of Transversal Skeletal And Dental Effects Of Bonded Rapıd Maxıllary Expansıon - Sevil Akkaya; Sumru Hızlan Lorenzon; Seda Haydar (Galenos Yayinevi, 1996)
During the present time, predominantly Hyrax appliance to which posterior bite planes have been added is widely used in the correction of bilateral posterior cross bites. This research was carried out in order to evaluate dental and skeletal effects of bonded rapid maxillary expansion appliance frontally. The material consisted of posteroanterior cephalograms; hand-wrist, occlusal radiographs which were taken from 12 patients having maxillary bilateral cross-bites. At the beginning of Treatment the average chronological age was 11.96 years. The treatment time varied from 0.7-1.60 months. At the end of active treatment the same appliance was worn for retentive purpose for an additional 3 months. When the findigns are evaluated throughout the research period; the values obtained for the transversal width of the upper first molars, maxillary skeletal width and nasal cavity width demonstrated that the main increase was between the transversal width of the upper first molars, and that the values decreased gradually when moving in an upward direction. Buccal tipping was found in the maxillary halves and upper first molars.